(untitled) (Proceedings of Southern Federal University. Philology, 2013)
Furdey O.N. Keywords: Russian immigrants’ journalism, world view, meaning of life, spirituality. The article studies M.Gorky’s views on the world and on man’s place in it. It describes some inconsistency in Gorky’s inner life, which reflected itself in his attitude to religion. The author studies the writer’s relationship with the intelligentsia who emigrated after the revolution and the further fate of the ‘Beseda’ magazine.